EIF3E–RSPO2 and PIEZO1–RSPO2 fusions in colorectal traditional serrated adenoma. Issue 2 (20th June 2019) - Hashimoto, Taiki; Ogawa, Reiko; Yoshida, Hiroshi; Taniguchi, Hirokazu; Kojima, Motohiro; Saito, Yutaka; Sekine, Shigeki
Abstract : Aims: Traditional serrated adenoma (TSA) is an uncommon type of colorectal serrated polyp. RSPO fusions, which potentiate WNT signalling, are common and characteristic genetic alterations in TSA. The aim of this study was to further characterise the prevalence and variation of RSPO fusions in TSA. Methods and results: Quantitative polymerase chain reaction (PCR) analysis of 99 TSAs revealed overexpression of RSPO2 and RSPO3 in six and 29 lesions, respectively. Reverse transcription PCR identified previously reported PTPRK – RSPO3 fusion transcripts in all 29 TSAs with RSPO3 overexpression, confirming that PTPRK – RSPO3 is the predominant RSPO fusion in TSAs. Among the six lesions with RSPO2 overexpression, two overexpressed full‐length RSPO2. An EIF3E – RSPO2 fusion, which is a known recurrent RSPO fusion in colorectal cancer, was detected in three lesions. In addition, rapid amplification of cDNA ends identified a novel PIEZO1 – RSPO2 fusion in one TSA. All of the four TSAs with RSPO2 fusions concurrently had KRAS mutations and showed the classic histological features. Conclusions: The present study identified EIF3E – RSPO2 and PIEZO1 – RSPO2 in TSAs. Our observations expand the spectrum of RSPO fusions in TSAs, and suggest that TSAs are precursors of colorectal cancers with these RSPO2 fusions.